(untitled) (Conference Zone, 2022)
According to scientists, pedagogy is the “art, science, or profession of teaching.” This broad definition covers various aspects of teaching, and there are many moving parts to pedagogy that include teaching styles, feedback, and assessment. The term pedagogy boils down to the study of different teaching methods. In this article discusses information about pedagogy in education systems and important aspects.